The Effect Combined Of Intradialytic Exercise: Static Stretching And Dynamic Streching Lower Limb, Increase Physical Funtion In Chronic Kidney Diseases On Haemodialysis Patients Quasi Experiment - Dewi, Desak Wayan Suarse Dewi (Holistic Nursing Plus, 2024)
Background: Individuals with end-stage kidney disease (ESKD) usually engage in minimal physical activity, as renal failure progresses in chronic kidney disease (CKD), muscle mass and physical function decrease. Physical activity (PA) is important in maintaining/improving health in all population. Aim of this study to evaluate effect exercise of combine static stretching and dynamic stretching increasing Physical Function in CKD on HD patients. Methods:  design of this  study was quasi experiment in one group 39 respondents CKD on HD patients meet inclusion criteria. Implementation 12 weeks intradialytic exercise combine static and dynamic stretching lower limbs include leg, ankles, knee, femoral and hip. During exercise evaluate using Borg Skill to know level of fatigue. Comparing with before-after test Time Up and Go 3 meters return measurement. Result: The results of this study demonstrate that the mean values of functional balance, which are much lower in this population than in their healthy counterparts, can be improved by a video-based intradialytic exercise program that includes stretching and endurance activities. In particular, notable advancements were noted in the average TUG test 3 meter return result, which is a reliable indicator of hospitalization, cardiovascular events, and mortality in dialysis patients. Conclusion all participants reported after 12 weeks static and dynamic stretching felt more flexible range of motion knee and leg, walking  stronger than before and felt more conformable in walking reported, significant different before and after given static and dynamic stretching, both Static and dynamic stretching effective for improving functional balance and physical performance, Recommended  static and dynamic stretching to be rutine activity in Hemodialysis unit.